Estimating Willingness to Pay for New Mandarin Cultivars: A Revealed Preference Approach - Xiang Bi; Lisa House; Zhifeng Gao; Frederick Gmitter (EDIS, 2014)
California has overtaken Florida to become the major US domestic mandarin producer. Despite a shift in consumer preferences toward the ‘Clementine’ mandarin that is widely grown in California, this cultivar is not well adapted to the subtropical climate of Florida. But in 2009, the University of Florida introduced the ‘Sugar Belle’, a cross between the ‘Clementine’ mandarin and the ‘Minneola’ tangelo. Survey test results showed that subjects preferred this new cultivar in terms of overall flavor, sweetness, acidity, and juiciness. survey test results showed that the Florida ‘Sugar Belle’ was preferred over the California ‘Clementine’ mandarin and the Florida ‘Murcott’ mandarin (aka Honey mandarin) in terms of overall flavor, sweetness, acidity, and juiciness. To determine consumer willingness to pay for specific attributes, UF/IFAS economists combined sensory evaluation and experimental auctions in a unique way, by comparing two different types of ‘Sugar Belle’ (SB1 and SB2) with the main competing product to identify the most desirable characteristics and to determine the best marketing and pricing strategy. This 6-page fact sheet was written by Xiang Bi, Lisa House, Frederick Gmitter, and Zhifeng Gao, and published by the UF Department of Food and Resource Economics, September 2014.